Ferulate-5-hydroxylase from Arabidopsis thaliana defines a new family of cytochrome P450-dependent monooxygenases. - Meyer, K (1996)
The fah1 mutant of Arabidopsis is defective in the accumulation of sinapic acid-derived metabolites, including the guaiacyl-syringyl lignin typical of angiosperms. Earlier results indicated that the FAH1 locus encodes ferulate-5-hydroxylase (F5H), a cytochrome P450-dependent monooxygenase (P450) of the general phenylpropanoid pathway. We have cloned the gene encoding this P450 by T-DNA tagging and have confirmed the identity of the cloned gene by complementation of the mutant phenotype. F5H shows 34% amino acid sequence identity with the avocado ripening-induced P450 CYP71A1 and 32% identity with the flavonoid-3',5'-hydroxylases of Petunia hybrida. In contrast, it shares much less homology with cinnamate-4-hydroxylase, a P450 that catalyzes the hydroxylation of cinnamic acid three steps earlier in the general phenylpropanoid pathway. Since the highest degree of identity between F5H and previously sequenced P450s is only 34%, F5H identifies a new P450 subfamily that has been designated CYP84.